Comparisons of financial hardship in cancer care by family structure and among those with and without minor children using nationally representative data - Jewett, Patricia I.; Purani, Himal; Vogel, Rachel I.; Parsons, Helen M.; Borrero, Maria; Blaes, Anne (Cancer medicine (Malden, MA), 2024)
Introduction While demographic risk factors of cancer‐related financial hardships have been studied, having minor children or being single have rarely been assessed in the context of healthcare‐related financial hardships. Methods Using data from the 2015 to 2018 National Health Interview Survey, we assessed financial hardship (material and psychological hardship; behavioral coping due to costs: delaying/foregoing care, reducing prescription costs, or skipping specialists or follow‐up care) among adults aged 18–59 years with cancer (N = 2844) by minor child parenting status and family structure. In a secondary analysis, we compared this group with individuals without cancer. Using logistic regression models, we compared those with and without children aged <18 years, further distinguishing between those who were single versus one of two or more adults in the family. Results Compared to individuals from families with two or more adults/without children, single adults with children more often reported cancer‐related financial hardships, for example material hardship (45.9% vs. 38.8%), and reducing prescription costs, (50.7% vs. 34.4%, adjusted OR 1.57, 95% CI 1.07–2.28). Single adults without minor children and those from families with two or more adults/with minor children also reported greater financial hardships on some dimensions. Associations were similar among those without cancer, but the overall magnitude of financial hardships was lower compared to those with cancer. Conclusions Our findings suggest that having minor children, and being a single adult are risk factors for cancer‐related financial hardship. Financial vulnerability associated with family structure should be taken into consideration in healthcare, and especially cancer care. We used 2015–2018 National Health Interview Survey data to assess the associations of having minor children or being single with healthcare‐related financial hardships among adults aged 18–59 years with and without a history of cancer. Compared to individuals from families with two or more adults/without children, adults with different family structures, and especially single adults with children, more often reported cancer‐related financial hardships (measured as [material and psychological hardship; behavioral coping due to costs: delaying/foregoing care, reducing prescription costs, skipping specialists or follow‐up care]). While these associations of family structure with financial hardships were similar in those with and without cancer, the overall magnitude of financial hardship was highest among those with cancer.